Policies, resistances and religious diasporas in a cross cultural perspective: evangelical Gypsies in Spain and Catholics Indigenous in Mexico - Cantón Delgado, Manuela; Gil Tébar, Pilar (Revista de Antropología Social, 2011)
Driving the emergence of new political actors, defining new mediations or resulting in resistances whose aim is to preserve tradition or confront their displacement, religious innovation continues to offer social scientists astonishing and constant splintering, transmutations, hybridity and new maps blurring the limits of what is thought about religions. This paper deals with two ethnographies in this perspective. One of these shows how Liberation Theology provides the indigenous population a forum in which they can find new models of co-existence. This is the aim of the work carried out by Pilar Gil in the dioceses of San Cristóbal de Las Casas, Chiapas (Mexico). The second focuses on the analysis of the embryonic political construction of the evangelical gypsy organisations from a multicentric approach, as well as its expansion in European and Latin American networks, and is the aim of the research Manuela Cantón has been carrying out for the last few years.
Keywords: Anthropology of Religion; Politics; Ethnicity